Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Cloning of the A Mating-Type Locus from Lepista nuda and Characterization of Its Genetic Structure - Chengbo Rong; Shuang Zhao; Dengjin Li; Lijuan Wang; Shouxian Wang; Kang Ma; Feng Xu; Yu Liu (Current Microbiology, 2015)

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity - Yuling Wu; Jia J. Li; Hyun Jun Kim; Xu Liu; Weiyi Liu; Ahmad Akhgar; Michael A. Bowen; Susan Spitz; Xu-Rong Jiang; Lorin K. Roskos; Wendy I. White (The AAPS Journal, 2015)

Retraction Note to: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Application of Lactic Acid Bacteria (LAB) in freshness keeping of tilapia fillets as sashimi - Rong Cao; Qi Liu; Shengjun Chen; Xianqing Yang; Laihao Li (Journal of Ocean University of China, 2015)

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Altered Functional Connectivity Patterns of the Insular Subregions in Psychogenic Nonepileptic Seizures - Rong Li; Kai Liu; Xujing Ma; Zhiqiang Li; Xujun Duan; Dongmei An; Qiyong Gong; Dong Zhou; Huafu Chen (Brain Topography, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Luteolin attenuate the d -galactose-induced renal damage by attenuation of oxidative stress and inflammation - Yuqing Xu; Jingzheng Zhang; Jing Liu; Sai Li; Cheng Li; Wen Wang; Rong Ma; Yi Liu (Natural Product Research, 2015)

SKF-96365 strongly inhibits voltage-gated sodium current in rat ventricular myocytes - Kui-Hao Chen; Hui Liu; Lei Yang; Man-Wen Jin; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

The role of Cyclin G1 in cellular proliferation and apoptosis of human epithelial ovarian cancer - Lifei Jiang; Rong Liu; Yingying Wang; Chunmiao Li; Qinghua Xi; Jianxin Zhong; Jian Liu; Shuyun Yang; Juan Wang; Menghui Huang; Chunhui Tang; Zheng Fang (Journal of Molecular Histology, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Establishment and characterization of a novel cell line from midgut tissue of Helicoverpa armigera (Lepidoptera: Noctuidae) - Jianghuai Li; Fei He; Yongbo Yang; Yutao Xiao; Rong Peng; Hanchao Yao; Xianchun Li; Jianxin Peng; Huazhu Hong; Kaiyu Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Over-expression of SlWRKY39 leads to enhanced resistance to multiple stress factors in tomato - Xiao-chun Sun; Yong-feng Gao; Hui-rong Li; Shu-zhang Yang; Yong-sheng Liu (Journal of Plant Biology, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)